Investment Model of Agricultural Biogas Plants for Individual Farms in Poland - Kamila Klimek; Magdalena Kapłan; Serhiy Syrotyuk; Nikolay Bakach; Nikolay Kapustin; Ryszard Konieczny; Jakub Dobrzyński; Kinga Borek; Dorota Anders; Barbara Dybek; Agnieszka Karwacka; Grzegorz Wałowski (Energies, 2021)
The main idea of a circular economy (CE) is to separate economic growth from resource consumption and environmental impacts. The characteristic approach of a CE assumes the minimisation of the amount of waste generated at the design level and, as a standard, includes innovations throughout the value chain. From an agricultural point of view, agricultural biogas plants are particularly important because they enable the management of all waste biomass and its conversion into useful energy and agricultural fertiliser. This paper presents methods for assessing the economic effectiveness of an investment in an agricultural biogas plant. The research goal was to develop a financial model. The authors of this study used available examples of the profitability of commercial ventures. We considered the investment aspects of agricultural biogas plants. Exemplary solutions are discussed, allowing the reader to become acquainted with various methods and proposals for thus far estimated investments. It may seem chaotic, but this is how the biogas market is characterised in the context of the implementation of biogas projects. Guidance is given regarding how to understand investing in this sensitive private farming sector. It is admirable that the renewable energy market has been systematised, and we hypothesise that it is necessary to develop an investment model in Polish conditions.